ENVIRONMENTAL CONDUCT ADJUSTMENT AGREEMENTS IN AMAZON - Ferreira, Adriana Passos; Simões, Helena Cristina Guimaraes Queiroz; Amoras, Fernando Castro (Veredas do Direito, 2023)
This research evaluated the repairing, preventing and compensating effectiveness of environmental conduct adjustment agreements proposed by states publics prosecutors. Hence, this study focused on verifying whether commitments undertaken by prosecution agencies have been able to reverse or at least minimize damages to the environment. For this, three conduct adjustment agreements were gathered for documentary analysis, being two from Amapá state and one from Pará state; both regions are within the eastern Amazon. These lands lie in the far north of Brazil, wherein the history on timber harvesting and environmental damages have been remarkable for decades. In two of the cases, terms were consistent with constitutional rules and environmental principles, setting deadlines for implementation of obligations and designation of agents who could assist in compliance of targets beyond the public prosecutor, highlighting causes of repairing nature. In the latter case, it was observed prioritization by different compensation solutions other than the ecological equivalent, featuring a low educational effect of the agreements, besides the lack of plans for environmental damage recovery.